Transparency of mosque financial reporting of ISAK 35 implementation on the Jami’ Al-Umary Mosque in Kelayu, East Lombok - Fitri, Himmatul (Proceeding International Conference on Accounting and Finance, 2024)
The purpose of this study was to determine the transparency of recording and financial carried out at the Jami’ Al-Umary Mosque in Kelayu. The study also to determine the conformity of the financial statements prepared by Jami’ Al-Umary Mosque Kelayu with ISAK 35. The data analysis technique in this study was qualitative data analysis with an interactive model. Based on the result of the study, it can be concluded that the financial reporting at the Jami’ Al-Umary Mosque Kelayu is carried out by simple recording based on the understanding of financial managers, transparency of the recording and financial carried out at the Jami’ Al-Umary Mosque in Kelayu in a social media mosque’s, announced every Friday on the mosque notice board, therefore all congregations can acsess it. The application of ISAK 35 at the Mosque has also not been implementation in accordance with the accounting principles that should apply to non-profit organization.